Influence of genetic variation on morphological diversity in accessions of Stevia rebaudiana Bertoni - Abdullateef, Raji Akintunde; Osman, Mohamad (Canadian Center of Science and Education, 2011)
Stevia rebaudiana, a non caloric natural sweetener is currently the available substitute to sugar. It is a genus of about 150 species of herbs and shrubs, a Compositae and a native to Paraguay. The aim of this study was to evaluate collected accessions of stevia and characterize their genetic divergence. In 2010, 10 stevia accessions were collected across different locations in Malaysia. At maturity they were evaluated using morphological parameters and collected data were subjected to‘t’ test analysis at p<.05 as follows-(i) Plant heights: MS012 & SBK were significant at p<.001 and p<.002 respectively. (ii) Number of branches: BGI & SBK were significant at p<.001 and p<.008 respectively.(iii) Number of corymbs: AZI was significant at p<.000, while BGI was significant at p<.033. (iv) Number of leaves: MS012 & MS007 were respectively significant at p<.000 and p<.008. (v) Plant leaf size: AZI was significant at p<.003, MS007 at p<.005, and MS012 at p<.019 and (vi) stem girth: MS012 & MRG were also significantly different at p<.000 and p<.001 respectively. MSO12, MS007 & SBK had loads of promising genetic traits in studied accessions.